MENUMBUHKAN JIWA KEPEMIMPINAN DARI ORGANISASI SEKOLAH - Nurokhim; Syaqiq, Muhammad; Amy Novalia Esmiati (3026-1791, 2025)
The implementation of the Basic Student Leadership Training (LDKS) program at Pondok Modern Selamat Batang High School aims to instill the values ​​of laughter and form a quality leadership spirit in students as the nation's next generation. Activities are carried out in three stages: preparation, implementation and evaluation. The program implementation took place on January 11 2025 with participants from OSIS, PMR, Paskibra, PKS, and PIK-R. The material presented covers three main topics: Leadership, Organizational Management, and Self-Control. The method used is material presentation and interactive discussion. Participants showed high enthusiasm in participating in the entire series of activities, marked by active participation in the question and answer session. It is hoped that the results of this program will be able to create a cadre of qualified and responsible leaders based on the values ​​of laughter, as well as preparing the next generation who have dignity and superior character to become future leaders.